2014
DOI: 10.1177/1473225413520361
|View full text |Cite
|
Sign up to set email alerts
|

Policy Issues Regarding the Overrepresentation of Incarcerated Aboriginal Young Offenders in a Canadian Context

Abstract: Over-representation of visible minority youth in youth prisons is evident in most advanced industrial and liberal democratic countries. In Canada, federal and provincial governments have initiated policy strategies to counteract the over-representation of Aboriginal offenders. One critical national initiative, the 2003 Youth Criminal Justice Act (YCJA), explicitly acknowledges the special status of Aboriginal youth. The current study examines (1) whether the YCJA has reduced the over-representation of Aborigin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 27 publications
0
37
1
Order By: Relevance
“…These include residential instability, low levels of education, high levels of unemployment, alcohol and substance use issues, poverty, and severe family conflict. 36,38 However, in the current study, even after adjusting for many of these risk factors, Aboriginal ancestry remained independently associated with incarceration, suggesting that policing practices or other aspects of the current criminal justice system may be partly responsible.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…These include residential instability, low levels of education, high levels of unemployment, alcohol and substance use issues, poverty, and severe family conflict. 36,38 However, in the current study, even after adjusting for many of these risk factors, Aboriginal ancestry remained independently associated with incarceration, suggesting that policing practices or other aspects of the current criminal justice system may be partly responsible.…”
Section: Discussioncontrasting
confidence: 54%
“…3941 In the context of the overrepresentation of Aboriginal youth in the criminal justice system, key relevant structural factors include the legacy of colonization and multi-century long, state-sponsored oppression. From the expropriation of land 37 , prohibition of language and cultural practices 42 , forcible removal of Aboriginal children into Church-run residential schools in the late 1800s onwards, 43,44 to the unaddressed intergenerational trauma 38,44 , continued economic marginalization, 36,38,44 and elevated rates of substance use and poverty today, 19,36,38 a myriad of factors contribute as underlying determinants of Aboriginal overrepresentation in prison populations. Indeed, an abundance of research has identified that Aboriginal peoples continue to experience marginalization and discrimination at much higher rates than non-Aboriginal peoples, 36,45,46 which appears to be consistent with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…In many ways, the criminal justice system experiences of Indigenous Australians appear to echo those of minorities in the USA and Canada, with similar minority overrepresentation in the chronic offender groups. Most notably, the patterns of Indigenous overrepresentation in the criminal justice system [9] mirror those we see among Black, Hispanic, and Native American populations in the USA [45] as well as those we see among Indigenous populations in Canada [25,101]. Indigenous Australians are overrepresented among offenders [17,62,89] and although they account for approximately 3 % of the population [10], they make up over 25 % of the country's adult prison population [9].…”
Section: Race/ethnicity and Life Course Offending Trajectoriesmentioning
confidence: 95%
“…This means that 84.5 % of non-Indigenous females never have any formal contact with the criminal justice system by age 25 years. Rates of system contact for nonIndigenous males and Indigenous females fall somewhere in the middle, with 40 % of Indigenous females and 45 % of non-Indigenous males having at least one system contact by age 25. In what follows, we describe how these patterns of contact unfold and vary from age 10 to age 25 both within and across groups disaggregated by gender and Indigenous status (independently and jointly).…”
Section: The Samplementioning
confidence: 97%
“…Fourth, whereas in the nineteenth and early twentieth centuries Indigenous peoples required permission from a colonial Indian agent to leave the reserve, containment continues through the prison system, where there are disproportionately higher rates of Indigenous peoples incarcerated and fewer Indigenous peoples being granted early parole compared with other groups (Corrado 2014;Owusu-Bempah et al 2014).…”
Section: Dhamoonmentioning
confidence: 99%